NMR and Chemometric Analysis of Verbascoside and Isoverbascoside Produced in Tecoma stans In Vitro Cultures - Paniagua-Vega, David (Magnetic resonance in chemistry : MRC, 2025)
© 2025 John Wiley & Sons Ltd.